Low Measured Hepatic Artery Flow Increases Rate of Biliary Strictures in Deceased Donor Liver Transplantation: An Age-Dependent Phenomenon. Issue 2 (February 2017) - Kim, Peter T. W.; Fernandez, Hoylan; Gupta, Amar; Saracino, Giovanna; Ramsay, Michael; McKenna, Gregory J.; Testa, Giuliano; Anthony, Tiffany; Onaca, Nicholas; Ruiz, Richard M.; Klintmalm, Goran B.
Abstract : Background: This study was conducted to determine effect of lower measured hepatic arterial (HA) flow (<400 mL/min) on biliary complications and graft survival after deceased donor liver transplantation. Hepatic artery is the main blood supply to bile duct and lack of adequate HA flow is thought to be a risk factor for biliary complications. Methods: A retrospective review of 1300 patients who underwent deceased donor liver transplantation was performed. Patients with arterial complications were excluded to eliminate potential contribution to biliary complications from HA thrombosis. Patients were divided into low (<400 mL/min; N = 201) and high (≥400 mL/min; N = 1099) HA flow groups. Incidence of biliary complications and graft survival were analyzed. Results: HA flows less than 400 mL/min were associated with increased rate of biliary strictures in younger donors (<50 years old), and in patients with duct-to-duct anastomoses ( P = 0.028). Lower HA flows were associated with decreased graft survival ( P = 0.013). Donor older than 50 years was associated with increased rate of biliary strictures (hazard ratio [HR], 1.67; 95% confidence interval [CI], 1.14-2.45; P = 0.0085) and graft failure (HR, 1.68; 95% CI, 1.35-2.1; P <0.0001) on multivariate analyses. HA flow less than 400 mL/min was associated with biliary strictures (HR, 1.53; 95% CI, 1.04-2.24; P = 0.0297) on univariate analysis only. Conclusions: HA flow less than 400 mL/min was associated with higher rate of biliary strictures in younger donors with duct-to-duct reconstruction and lower graft survival. A consideration should be given to increase the intraoperative HA flow to prevent biliary strictures in such patients. Abstract : In a large, meticulously documented study of hepatic hemodynamics in liver transplantation, the authors identified a correlation between decreased hepatic arterial flow and the risk for biliary stricture that is potentiated by increasing donor age.